Temperature dependency of aqueous biphasic systems: An alternative approach for exploring the differences between Coulombic-dominated salts and ionic liquids - E Silva, Francisca A.; Pereira, Jorge F. B. [UNESP]; Kurnia, Kiki A.; Ventura, Sónia P. M.; Silva, Artur M. S.; Rogers, Robin D.; Coutinho, João A. P.; Freire, Mara G. (Royal Society of Chemistry (RSC), 2017)
Herein we propose an alternative way to distinguish ionic liquids from Coulombic-dominated salts, based not on their upper limit melting temperature (100 °C), but on the trend of their phase-forming abilities to create aqueous biphasic systems as a function of temperature, in which a wider plethora of interactions can be appraised.